Design of an Intelligent Processing System for Business Data Analysis Based on Improved Clustering Algorithm - Wang, Ning (Procedia computer science, 2023)
In order to further optimize the processing of business data and increase the effectiveness and accuracy of business data analysis, this research investigated the design of an intelligent processing system for business data analysis based on improved clustering algorithms. Some issues with business data analysis can be efficiently resolved by enhancing clustering algorithms, resulting in the provision of more intelligent, thorough, and precise business data analysis services for businesses and organizations. The improved clustering algorithm is compared with the traditional clustering algorithm to analyze the experimental data, the results showed that the maximum clustering effect of the improved clustering algorithm was above 80%, the highest robustness was 91.65%, and the highest point in algorithm performance was 90.97%. From these three aspects, it can be seen that improved clustering algorithms have more advantages than traditional clustering algorithms. Therefore, improving clustering algorithms can make business data processing more efficient, accurate, and reliable, providing enterprises and organizations with higher quality business data analysis services.